1991
DOI: 10.1071/rd9910551
|View full text |Cite
|
Sign up to set email alerts
|

Increased production of sheep embryos following superovulation of Merino ewes with a combination of pregnant mare serum gonadotrophin and follicle stimulating hormone

Abstract: In a factorially designed experiment (N = 321), 0, 800 or 1600 I.U. pregnant mare serum gonadotrophin (PMSG) were administered in combination with 0, 12 or 18 mg follicle stimulating hormone (FSH-P) to superovulate Merino ewes in autumn and spring. A moderate dose of PMSG (800 I.U.) in conjunction with 12 or 18 mg FSH-P increased the ovulation rate above that observed when FSH-P was used alone. This was accomplished by (i) increasing the proportion of ewes that exhibited a superovulatory response (greater than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
27
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 0 publications
4
27
0
Order By: Relevance
“…Similar results have been reported in ewes [10] and goats [11]. However, prematurely regressed CL has been observed in suprovulated ewes [12][13][14], cows [15] and goats [16][17][18]. Ryan et al [13] reported that the proportion of ewes that ovulated and subsequently had M chorionic gonadotropin (eCG) has been conventionally used for superovulation in ewes [1][2][3][4].…”
supporting
confidence: 65%
See 2 more Smart Citations
“…Similar results have been reported in ewes [10] and goats [11]. However, prematurely regressed CL has been observed in suprovulated ewes [12][13][14], cows [15] and goats [16][17][18]. Ryan et al [13] reported that the proportion of ewes that ovulated and subsequently had M chorionic gonadotropin (eCG) has been conventionally used for superovulation in ewes [1][2][3][4].…”
supporting
confidence: 65%
“…Premature luteal regression has been reported in superovulated ewes [12][13][14]22], and has impaired the yield of normal fertilized embryos. Jabbour et al [12] and Ryan et al [13] reported that more ewes had regressed CL in autumn (24% and 37%, respectively) than in spring (6% and 21%, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inadequate luteal function has also been reported in superovulated ewes following oestrous synchronization using a dual prostaglandin injection treatment (Trounson et al, 1976;Schiewe et al, 1991). In embryo donor ewes, the incidence of premature luteal regression after a progestagen protocol and superovulation seems to be higher in the seasonal anoestrus than in the breeding season, even at temperate latitudes (Jabbour et al, 1991;Ryan et al, 1991). Corpora lutea from ewes undergoing premature luteolysis have a reduced population of small luteal cells compared to normal corpora lutea (Schiewe et al, 1991).…”
Section: Luteal Activitymentioning
confidence: 99%
“…In fact, early luteal regression is assumed as a failed response to superovulation and has also been reported by our group in both Rasa Aragonesa and Ojalada breeds (Forcada et al, 2000(Forcada et al, , 2006(Forcada et al, , 2011a, although always associated with multiple FSH injection protocols, not including eCG (Simonetti et al, 2008;Forcada et al, 2011b). This regression after superovulatory treatments seems to be related with a lack of progesterone priming before treatment, so that its incidence should be higher during anestrus (Ryan et al 1991). Some authors have indicated that a simplified superovulatory FSH protocol produced the higher percentage of premature CL regression (Riesenberg et al, 2001) with no eCG in the treatment.…”
Section: Introductionmentioning
confidence: 93%